Dampak Pengelolaan Sampah Plastik terhadap Lingkungan Perkotaan - Sita Prabasari Bandowo; M. Farid Dimjati Lusno (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Plastic waste management has become an increasingly urgent environmental issue in urban areas due to the rising production and consumption of plastic materials. This study aims to analyze the impact of plastic waste management on the urban environment through a systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach. Articles were retrieved from Google Scholar, PubMed, and ScienceDirect based on predetermined inclusion criteria. The findings indicate that plastic waste management in urban areas still faces multiple challenges, including weak policy implementation, limited infrastructure, and low community participation. Environmental impacts include soil and water pollution, blockage of drainage systems that may lead to flooding, and health risks associated with plastic waste burning. However, several best practices, such as single-use plastic reduction policies and community education programs, have shown positive outcomes. This study highlights the importance of a multidimensional approach that integrates policy development, education, and active community participation to achieve sustainable plastic waste management in urban environments.